The Impact of Recognition Versus Disclosure on Financial Information: A Preparer's Perspective - CLOR‐PROELL, SHANA M.; MAINES, LAUREEN A. (Journal of Accounting Research, 2014)
ABSTRACT We investigate whether recognition on the face of the financial statements versus disclosure in the footnotes influences the amount that financial managers report for a contingent liability. Using an experiment with corporate controllers and chief financial officers, we find that financial managers in public companies expend more cognitive effort and exhibit less strategic bias under recognition than disclosure. This difference appears to be associated with capital market pressures experienced by public company managers as we find that both the cognitive effort and bias exhibited by private company managers are unaffected by placement. As a result, public company managers make higher liability estimates for recognized versus disclosed liabilities. Their liability estimates are similar to those of private company managers for recognition but lower than private company managers’ estimates for disclosure. Our results have implications for auditors and financial statement users in evaluating recognized versus disclosed information for public and private companies.